Factors Affecting Cost Stickiness in Manufacturing Companies Listed on the IDX for the 2016-2022 Period - Wulandari, Inayah; Ulfah, Yana (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to examine sales growth, asset intensity, employee intensity, and leverage on cost stickiness in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2022 period. The type of research is quantitative using secondary data. The sampling technique uses the purposive sampling method with a total of 65 manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2022 period. The data analysis used is SPSS 25 software. The results of this study are that sales growth and asset intensity have a positive and significant effect on cost stickiness, employee intensity has a positive but not significant effect on cost stickiness, and leverage has a negative and significant effect on cost stickiness